Sistem Penggajian dan Tunjangan Kerja di PT.Bumitama Gunajaya Agro Region Pundu Kalimantan Tengah - Zulfahnur, Afifah; Listiyani; Ferhat, Amallia (Program Studi Agribisnis INSTIPER Yogyakarta, 2023)
The aim of this research is to investigate the mechanisms employed in the remuneration system at PT. Bumitama Gunajaya Agro Pundu Estate. The fundamental method used in this research involves a descriptive analysis utilizing both qualitative and quantitative approaches. The research sample consists of 32 employees, comprising 8 staff members and 24 non-staff members, selected from the Microbiology Laboratory unit. The data collected encompasses primary information concerning the remuneration system, allowances, and other numerical data that can be processed. Secondary data is obtained through the collection of documents associated with Standard Operating Procedures (SOP). Remuneration for staff members is determined based on their tenure, position, Key Performance Indicators (KPIs), and negotiations. In contrast, the remuneration for non-staff employees is established according to attendance records, job descriptions, responsibilities, and incentives.